Extração, caracterização estrutural parcial e atividades farmacológicas do olginato obtido da alga marrom Lobophora variegata (Lamouroux) Oliveira Filho, 1977 - Almeida, Hugo Wescley Barros (2014)
The alginic acid or alginates are acidic polysaccharides found in brown seaweed widely used in food, cosmetic, medical and pharmaceutical industry. This paper proposes the extraction, chemical characterization and verification of the pharmacological activities of brown seaweed variegata Lobophora . The alginate was extracted from the seaweed Lobophora variegata and part was sulphated for comparative purposes. The native extract showed 42% total sugar, 65% uronic acid, 0,36 % protein and 0% of sulfate, while the sulfate showed 39% , 60%, 0.36% and 27,92 % respectively. The presence of a sulfate group may be observed by the metachromasia with toluidine blue in electrophoresis system and characteristic vibration 1262,34 cm-1 in infrared spectroscopy connections assigned to S = O. We observed the formation of films and beads of native alginate, where more concentrated solution 6% resulted in a thicker and more consistent film. Native alginate showed proliferative activity at concentrations (25 and 50 mcg), (50 mg) and (100 mg) in 3T3 cell line in 24h, 48h and 72h, respectively , as the sulfated (100 mg) in 24 . Also showed antiproliferative or cytotoxic activity in HeLa cells of strain, (25 and 100 mg), (25 and 100 mg) and (25, 50 and 100 mg), to native, now for the sulfate concentrations (100 mg) in 24 (25, 50 and 100 mg) in 48 hours, and (50 and 100 mg ) 72h. For their antioxidant activity, the sulfated alginates have better total antioxidant activity reaching 29 % of the native activity while 7.5 % of activity . For the hydroxyl radical AS showed high inhibition ( between 77-83 % ) in concentrations, but the AN surpassed these numbers in the order of 78-92 % inhibition. The reducing power of AN and AS ranged between 39-82 % . In the method of ferric chelation NA reached 100 % chelating while the AS remained at a plateau oscillating 6.5%. However, in this study , we found alginates with promising pharmacological activities, to use in various industries as an antioxidant / anti-tumor compound